Deformation mechanism and dynamic stability of the subgrade landslide considering evolution of friction-cohesion in slip zone - Deng, Yingxiang; Zhao, Mengdi; Luo, Tao; Zhou, Yunwen (Frontiers in Earth Science, 2025)
The excavation of high-speed subgrade has formed a large number of subgrade landslides, which have always been a potential threat to highway traffic, and the stability of landslides has an important impact on ensuring the normal operation of highways and traffic safety. In this paper, the on-site engineering geological investigation of a high-speed subgrade landslide is carried out, and the ring shear test is carried out by taking soil samples from slip zone, and the evolution relationship between the friction angle and cohesion in slip zone soil with shear displacement is analyzed by using the Moore-Coulomb theory, and the dynamic evolution law of the shear strength of slip zone soil is revealed. Combined with the typical residual thrust model and the finite element numerical model, the deformation failure mechanism and dynamic stability of the landslide were systematically analyzed. The following conclusions were drawn: The landslide slid again under the inducement of rainfall and gravity, and the overall performance was collapse-slip failure. The friction angle in slip zone soil shows the attenuation trend of the logistic model, and the cohesion shows the attenuation trend of the power function model. With the continuous deformation of landslide, the deformation displacement of landslide gradually showed an increasing trend, and the deformation of the slip zone gradually penetrated from the leading edge and the trailing edge, and the simulation results were basically consistent with the results of the landslide field investigation. With the increase of landslide displacement, the stability of landslide gradually decreases from the peak stability, and finally maintains the residual stability, which is between 1.07 and 1.08. Monitoring and early warning measures should be carried out at any time in the later stage. The landslide stability evaluation has an important safety early warning effect on the normal operation and traffic safety of the expressway.